Denied at Every Turn: A Literature Review of the Barriers in the ODSP Application Process - Karaceper, Senem; Dhugga, Prabjot; Goudar, Poornima; Komarniski, Robin; Zaki, Naveera (Prepared by the McMaster Research Shop for the Disability Justice Network of Ontario, 2025)
This report presents findings from a project conducted by the McMaster Research Shop for the Disability Justice Network of Ontario (DJNO). DJNO is a non-profit organization located in Hamilton, Ontario, with a mission to build a just and accessible Ontario where disabled people are empowered. One area of DJNO's advocacy focuses on the Ontario Disability Support Program (ODSP), which provides financial assistance, medical and employment support to disabled people. Initial evidence suggests that disabled communities in Ontario may face various barriers when accessing the ODSP and navigating related tribunal processes, which prompted this investigation. The purpose of this research was to examine potential accessibility challenges in the ODSP application and related tribunal and legislative processes, with particular attention to the experiences of disabled people, and more specifically, Black, Indigenous, and racialized disabled populations.